Genome-wide association study identifies several loci for HEV seropositivity - Maria K., Smatti (2023)
Hepatitis E viral (HEV) infection imposes a heavy global health burden. The variability in the prevalence of serological markers of HEV infection between different ethnic groups proposes a host genetic influence. Here, we report genetic polymorphisms associated with anti-HEV antibody positivity and level using binary- and quantitative-trait genome-wide association studies (GWAS) on a population from Qatar (n = 5829). We identified a region in 12p11.1 (lead SNP: rs559856097, allele: A, p = 2.3 × 10−10) significantly associated with anti-HEV antibodies level. This intergenic variant is located near SNORD112, a small nucleolar RNA (snoRNA). Additional gene-set and pathway enrichment analyses highlighted a strong correlation with anti-viral response-related pathways, including IFNs (alpha/beta) and interleukin-21 (IL-21) signaling. This is the first GWAS on the response to HEV infection. Further replication and functional experimentation are warranted to validate these findings.